(untitled) (CIPEEX, 2025)
Palliative care consists of actions aimed at reducing suffering while promoting comfort and dignity for patients with serious or terminal illnesses. The nursing professional plays a fundamental role in providing palliative care, acting as an essential link between the patient, the family, and the healthcare team. With training focused on holistic care and the promotion of quality of life, nurses are equipped to recognize the physical, emotional, social, and spiritual needs of patients facing serious or terminal illnesses. This study aimed to investigate and analyze the care provided by nurses to patients in palliative care. As a research tool, interviews were conducted with 15 nurses of both genders, aged between 24 and 49, at a hospital in the city of Ceres. The analysis revealed varying perceptions of the role of nurses in pain management for palliative care patients. While nurses consider pain management important, it is often viewed as secondary since prescribing medications is the responsibility of physicians. However, this overlooks nurses’ significant contribution in monitoring patients and managing symptoms. Nurses were found to be fundamental in providing emotional and psychological support, adopting a holistic approach that extends beyond physical symptom management. They also promote dignity and respect for patients, using empathetic and respectful communication to align care with patients’ preferences and values. It is concluded that nurses play a multifaceted role in palliative care, combining technical and interpersonal skills to positively influence patients’ quality of life, ensuring comprehensive, humanized, and effective care.